Hubungan Berwudhu Sebelum Tidur dengan Kualitas Tidur Santri Remaja Sekolah Menengah Atas yang Tinggal di Pondok Pesantren - Hanafi, Moh; Ridwan, Moh; Nur Izzati, Aisyah; Mulya Nugraha, Luqman (STIKES Ngesti Waluyo, 2024)
Sleep is essential for human life. Poor sleep quality negatively affects the physiological and biological aspects of adolescents. Performing ablution before sleep is one way to achieve good sleep quality. Ablution before sleep provides a relaxing effect on the body and a sense of calm, which is conducive to sleep. This study aims to examine the relationship between performing ablution before sleep and the sleep quality of teenage students living at the Damarjati Islamic Boarding School in Kaliangkrik. The study employed an analytical observational design with a cross-sectional approach. The research subjects were high school teenage students residing in the Damarjati Islamic Boarding School, with a sample size of 66 respondents. The chi-square test was used as the correlation test. The findings revealed that 27 respondents (40.6%) had good sleep quality, while 39 respondents (59.1%) experienced poor sleep quality. Among them, 36 students (54.5%) performed ablution before sleep, while 30 students (45.5%) did not. The study results showed a p-value of 0.000, indicating a significant relationship between performing ablution before sleep and sleep quality. There is a significant relationship between performing ablution before sleep and the sleep quality of teenage students living at the Damarjati Islamic Boarding School in Kaliangkrik. For future research, it is recommended to include additional variables that may influence sleep quality and to measure sleep quality using brainwave analysis.